PHYTOCHEMICAL QUANTIFICATION OF PRIMARY AND SECONDARY METABOLITES OF MYRISTICA FRAGRANS (H.) ETHANOLIC SEED EXTRACT - RANCY ANN THOMAS,; DR. S KRISHNAKUMARI,; RANCY ANN THOMAS, (International Journal of Pharma and Bio Sciences, 2015)
The therapeutic use of herbs is as old as human civilization and has evolved along with it. A vast majority of people on this planet still rely on their indigenous system of medicine and use herbal drugs. The Indian and Chinese systems of medicine are well established with written records going back around 3000 years. Medicinal plant drug discovery continues to provide new and important leads against various pharmacological targets, including cancer, malaria, cardiovascular diseases and neurological disorders. Interest in herbal drugs and natural medicine is undergoing a renaissance at the present time. The medicinal properties of plants are due to the presence of active principles such as alkaloids, phenolics, tannins and flavonoids which constitute of many pharmacologically active compounds. The aim of the present study was to quantify the presence of a few primary and secondary metabolites in the nutmeg seeds.The results of phytochemical screening of ethanolic seed extract of Myristica fragrans revealed the presence of primary metabolites like carbohydrates, proteins and amino acids and secondary metabolites such as alkaloids, flavonoids, tannins and phenols. The high level of primary metabolites in the sample reveals its nutritive value. These secondary metabolites could be responsible for the observed medicinal properties of Myristica fragrans by traditional herbalists.